The effects of an educational program based on the health belief model on information-motivation-skill-behavioral skills among women living with human immunodeficiency virus - Zahra Bayat Jozani; Minoo Mohraz; Mostafa Qorbani; Touran Bahrami Babaheidari; Zohreh Mahmoodi (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Human immunodeficiency virus (HIV) is a kind of behavioral disease in that adopting behavioral changes is the only way to control and stop the epidemic. The aim of this study is to investigate the effect of education base on the health belief model (HBM) on health-seeking behavior among HIV-positive women. MATERIALS AND METHODS: This study is a paralleled, randomized controlled clinical trial done with control group among HIV-positive women who were registered at the voluntary and counseling testing center of Imam Khomeini hospital in Tehran. Data were gathered by using information obtained from the Motivation-Skill-Behavior questionnaire and demographic data. The women were divided by permuted block and were randomized into two groups. Interventional group participated in six HBM educational classes and used routine counseling guidelines, but the control group used only routine counseling protocol. Data were collected before, immediately after, and 3 weeks after interference among all participants. Data were analyzed by using SPSS software version 16. RESULTS: According to the results and statistical test, before intervention, the mean score of knowledge was not significantly different in the two groups, but after intervention in the interventional group, test result and follow-up increased statistically significantly (P = 0.000). Both groups had increased mean score of knowledge, and there is significant trend in level of knowledge(interventional group 20.79 ± 1.88, control group: 17.36 ±2.44) and there was a significant increase in mean attitude follow-up score (P < 0.001). CONCLUSION: According to the result of the present study, counseling base on HBM by trained educator can increase information-motivation-skill-behavior among women living with HIV.